2016
DOI: 10.1097/mnm.0000000000000522
|View full text |Cite
|
Sign up to set email alerts
|

Combined imaging with 68Ga-DOTA-TATE and 18F-FDG PET/CT on the basis of volumetric parameters in neuroendocrine tumors

Abstract: Ga SRI and F-FDG PET/CT provide complementary information on treatment protocol and response assessment. While assessing the prognosis and tumor aggressiveness, lesions and whole-body tumor burdens can be calculated on the basis of volumetric parameters by F-FDG PET/CT using MTV and TLG, and by Ga SRI using somatostatin receptor density and TLSRE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 23 publications
1
51
1
Order By: Relevance
“…Total 68 Ga-DOTATATE uptake in NETs was reported in the past in a series of patients, but not in specific subtypes of NET, and no correlation analysis with tumor biomarkers was reported [12,13]. Moreover, the correlations between tumor biomarkers and tumor burden reported in the past have been based on anatomical imaging[19], counting the number of lesions[10], presence/absence of liver metastases[25] and not based on accurate total tumor volume measurements, as performed in the current analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total 68 Ga-DOTATATE uptake in NETs was reported in the past in a series of patients, but not in specific subtypes of NET, and no correlation analysis with tumor biomarkers was reported [12,13]. Moreover, the correlations between tumor biomarkers and tumor burden reported in the past have been based on anatomical imaging[19], counting the number of lesions[10], presence/absence of liver metastases[25] and not based on accurate total tumor volume measurements, as performed in the current analysis.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no study has yet assessed the utility of biochemical biomarkers for evaluating NET burden using the new generation DOTA-peptide based PET/CT imaging [12,13]. Thus, in this study we analyzed the correlation between biochemical biomarkers of NETs and total 68 Ga-DOTATATE-avid tumor volume (TV), as a measure of total tumor burden in patients with NET.…”
Section: Introductionmentioning
confidence: 99%
“…Abdulrezzak et al [52] gave a contribution to the combined imaging approach with [ 68 Ga]Ga-DOTA-TATE and [ 18 F]FDG by measuring several volumetric parameters instead of SUV max only, as there are many factors that can influence this parameter. These new parameters are the metabolic tumor volume (MTV) and the total lesion glycolysis (TLG) values in [ 18 F]FDG PET/CT), the somatostatin receptor density (SRD) and the total lesion somatostatin receptor expression (TLSRE) values in [ 68 Ga]Ga-DOTA-TATE PET/CT.…”
Section: Combined [68ga]ga-dota-sst Analogues and [18f]fdg Pet/ct mentioning
confidence: 99%
“…These 18 F-FDG PET/CT parameters also correlate with PFS, OS and in one study had a sensitivity and specificity for differentiating G1/G2 tumors form G3 of 100% and 62%, respectively(Table 6). A number of studies have concluded that the results of 18 F-FDG PET/CT and 68 Ga-DOTA-SSA PET/CT provide complementary information that is clinical relevant[24,136,142145]. Recent studies[139,140] have extended this principal of the complementariness of these to nuclear medicine imaging studies to recommend a NETPET score be assigned to NETs based on the result of these two studies that could have important prognostic value and help select better therapeutic options.…”
Section: Molecular Imaging In Pannets(table 2) (Fig 1)mentioning
confidence: 99%